Impact of Ergonomic Awareness on Ocular Strain, Dry Eye Symptoms, and Postural Discomfort in Laptop-Using Office Workers - Muhammad Akmal ,; Muhammad Ajmal ,; Muhammad Afzal,; Muhammad Ahsan Raza ,; Muhammad Ahmed,; Mukhtiar Hussain , (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Prolonged laptop use is increasingly associated with ocular strain, dry eye symptoms, and work-related musculoskeletal discomfort. While ergonomic interventions are known to reduce these complaints, the independent role of ergonomic awareness in preventing visual and postural problems remains underexplored. Objective: To assess the impact of ergonomic awareness on the prevalence of ocular strain, moderate-to-severe dry eye symptoms, and postural discomfort among office workers who routinely use laptops. Methods: This analytical cross-sectional study was conducted from June 2023 to May 2024 at Shaikha Fatima Institute of Nursing and Health Sciences, Shaikh Zayed Medical Complex, Lahore, and Jining Medical University, China. A total of 100 office employees completed a structured questionnaire including demographic information, the Ergonomic Awareness Score (EAS), a Computer Vision Syndrome symptom checklist, the Ocular Surface Disease Index (OSDI), and the Modified Nordic Musculoskeletal Questionnaire. Participants were categorized into low, moderate, and high ergonomic awareness groups. Statistical analyses included chi-square tests and multivariable logistic regression. Results: Ocular strain affected 68% of participants, moderate-to-severe dry eye symptoms were present in 45%, and postural discomfort was reported in 61%. Higher ergonomic awareness was significantly associated with lower prevalence of all symptoms. After adjustment, high awareness independently reduced the odds of ocular strain (aOR 0.38), dry eye symptoms (aOR 0.42), and postural discomfort (aOR 0.36). Daily laptop use exceeding eight hours remained an independent risk factor. Conclusion: Higher ergonomic awareness substantially reduces ocular and musculoskeletal complaints among laptop-using office workers. Structured ergonomic education should be integrated into workplace health programs to promote visual and postural well-being.